Dinamika Makanan Tradisional Tapa Kolo - Rafaela Ratrosnin, Serafina; Aliffiati, Aliffiati; Murniasih, Anak Agung Ayu (Sunari Penjor : Journal of Anthropology, 2019)
Tapa kolo is interpreted as bamboo rice that is burned. Rice-based Tapa Kolo. Traditional Tapa kolo meals are usually served at sacred ceremonies. Before the grilled first was prayed for by the customs.  At the time of traditional ceremony, among bamboo rice burned there "Kolo Wada kudut Helang ata pa'ang be le" means bamboo rice to be presented to the ancestors. The theory used is the function theory of Foster and Anderson. The concept used is the dynamics and traditional food of tapa kolo. Methods used qualitative research methods with ethnographic research models through observation techniques, interviews, and library studies. Research-supporting instruments are interview guidelines, voice recording tools, cameras, and stationery. Traditional Food Tapa Kolo experienced the dynamics caused by several factors. Nevertheless the existence of traditional food of Tapa Kolo is still preserved by the people of Liang Ndara village. In addition to the traditional food that is sacred tapa kolo, this traditional food is served profunently. The traditional food of Tapa Kolo is profanally presented to the tourists who come to the village of Liang Ndara.